Assessment Of Technical Efficiency Of Selected Commercial Banks In Ethiopia - Getenat H/Michael (My University, 2015)
The main aim of this study was to measures the relative efficiency of selected commercial banks in Ethiopia for the period of 2007 to 2013 with an integrated approach includes Data Envelopment Analysis (DEA) and Malmquist index. The researcher employed Data Envelopment Analysis (DEA) and Malmquist index to measure the extent of overall technical, pure technical,scale efficiencies and productivity of selected commercial banks in Ethiopia. And under the study the quantitative data type, secondary source and purposive sampling methods were used. Using Data Envelopment Analysis (DEA) and Malmquist index, in this study aims to measure the extent of overall technical, pure technical, scale efficiencies and productivity in eight commercial banks of Ethiopia with operating experience of seven years starting from 2007 up to 2013. CCR and BCC models under input oriented method were used to arrive at their technical efficiencies. The empirical findings reveal that during the study period BOA were the lowest scorer of overall technical efficiency of 73.4%, i.e., input could be reduced by 26.6% without sacrificing output if BOA were efficient. The lowest score of pure and scale efficiency were 81% and 80.8% by AIB and CBB during the study period. The average Malmquist index of the banks was 94.8% these decrease in overall productivity of banks resulted because of an average 0.01% decrease in scale efficiency and average of 5.1% decrease in technology adaptation by the banks during the study periods. Key words: Data Envelopment Analysis, Malmquist index, Technical Efficiency, Pure Technical Efficiency, Scale Efficiency.